Air‐Sea Turbulent Heat Flux Feedback Over Mesoscale Eddies - Sophia Moreton; David Ferreira; Malcolm Roberts; Helene Hewitt (Geophysical Research Letters)
Abstract Air‐sea turbulent heat fluxes play a fundamental role in generating and dampening sea surface temperature (SST) anomalies. To date, the turbulent heat flux feedback (THFF) is well quantified at basin‐wide scales (∼20 Wm−2K−1) but remains unknown at the oceanic mesoscale (10–100 km). Here, using an eddy‐tracking algorithm in three configurations of the coupled climate model HadGEM3‐GC3.1, the THFF over mesoscale eddies is estimated. The THFF magnitude is strongly dependent on the ocean‐to‐atmosphere regridding of SST, a common practice in coupled models for calculating air‐sea heat flux. Our best estimate shows that the mesoscale THFF ranges between 35 and 45 Wm−2K−1 globally, across different eddy amplitudes. Increasing the ratio of atmosphere‐to‐ocean grid resolution can lead to an underestimation of the THFF, by as much as 80% for a 6:1 resolution ratio. Our results suggest that a large atmosphere‐to‐ocean grid ratio can result in an artificially weak dampening of mesoscale SST anomalies.